Kecerdasan Emosional dan Spiritual terhadap Kesehatan Mental Mahasiswa - M. Rezki Aulia Rahman; Suhermi; Ernasari; Sudarman; Akbar Asfar (Window of Nursing Journal, 2024)
Mental health is a health problem that cannot be underestimated because it will indicate big problems such as violent behavior, depression and even suicide. Based on Basic Health Research (Riskesdas) 2018 data, it is known that more than 19 million Indonesians have mental disorders and depression. This study aims to determine the effect of emotional and spiritual intelligence on the mental health of Indonesian Muslim university nursing students class of 2021. This research is a quantitative study using a cross-sectional approach in the Indonesian Muslim university nursing study program. The population of this study was 65 people and the sample was taken using the total sampling method. The tests in this study were chi square analysis with the level of food (ρ > 0.05). The result of this research is that there is a significant effect between emotional intelligence on mental health ρ = 0.002 and there is a significant effect between spiritual intelligence on mental health ρ = 0.000. The conclusion from this study is that there is a significant influence between emotional and spiritual intelligence on students' mental health. Therefore, through this research, students are advised to take new lessons in order to gain knowledge directly and as material for self-evaluation in the future related to emotional, spiritual and mental problems.